A mixed-effects model approach for the statistical analysis of vocal fold viscoelastic shear properties. (November 2017) - Xu, Chet C.; Chan, Roger W.; Sun, Han; Zhan, Xiaowei
Abstract: A mixed-effects model approach was introduced in this study for the statistical analysis of rheological data of vocal fold tissues, in order to account for the data correlation caused by multiple measurements of each tissue sample across the test frequency range. Such data correlation had often been overlooked in previous studies in the past decades. The viscoelastic shear properties of the vocal fold lamina propria of two commonly used laryngeal research animal species (i.e. rabbit, porcine) were measured by a linear, controlled-strain simple-shear rheometer. Along with published canine and human rheological data, the vocal fold viscoelastic shear moduli of these animal species were compared to those of human over a frequency range of 1–250 Hz using the mixed-effects models. Our results indicated that tissues of the rabbit, canine and porcine vocal fold lamina propria were significantly stiffer and more viscous than those of human. Mixed-effects models were shown to be able to more accurately analyze rheological data generated from repeated measurements. Highlights: Mixed-effects model approach for the analysis of vocal fold rheological data. Different mixed models can be used to analyze different viscoelastic shear moduli. Log-transformation can increase the normality of the vocal fold rheological data. Rabbit, dog and pig vocal folds are significantly stiffer than those of human. Rabbit, dog and pig vocal folds are significantly more viscous than those of human.